Students’ Self Regulated Thinking Profiles In Overcoming Math Problems - Dewi Asmarani; Musrikah Musrikah (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2022)
The results of tests conducted by PISA and TIMSS expose that students’ mathematics mastery in Indonesia included in low category. The students show difficulties in processing their thought and solving problems to understand mathematics concepts. By then, this study aims to analyze the students’ thinking process in solving mathematics matters. The researcher identified clearly and in detail about Self Regulated Thinking (SRT) for some students who had succeeded in solving math questions. The research design applied in the present study is case study. The data and data sources are the results of data test for eight grade 15 years old students. The results showed that the students basically have skills in monitoring their own thoughts, determining appropriate problem solving plans, identifying and using the existing learning sources, providing responses or feedback, and evaluating the effectiveness of their own actions. The students also expressed different styles in implementing self regulated thinking (SRT). Accordingly, mathematics teachers need to design mathematics lesson that provides opportunity for students to express and improve their thinking skills